Konsentrasi Efektif (EC50-1Jam) Ekstrak Akar Tuba (Derris elliptica) Sebagai Bahan Anestesi Benih Ikan Mas (Cyprinus carpio) - Affandi Amirullah; Eko Efendi; Mahrus Ali (Jurusan Perikanan dan Kelautan, 2014)
Tuba (Derris elliptica) root was used traditionally as a poison to fish catching. This research looks for beneficial of tuba root extract as an anesthetic for the transport of fish seed. This research aims was to explore the value of effective concentration (EC50 - 1 hr) of tuba root extracts by ethanol and hexane, as well as determine the effect of the effective concentration value and the period of transportation time on the survival and growth of common carp seed. Probit analysis used to determine the effective concentration , whereas to determine the effect of differences of periods of transportation (2 , 4 and 6 hours) and the value of the effective concentration of each solvent on the survival and growth of the research design uses factorial analisis. The results of probit analysis for ethanol and hexane solvent are 6.166 and 3.72 ppm. Transportation showed the highest survival rate at treatment of transportation period 2 hour with values ​​reaching an average of 100%, while the highest growth occurres in hexane treatment on the period of transportation of 6 hours. This results also found that the period of transportation differences significantly affect the survival of common carp seeds but has no significant effect on the growth of common carp other results showed that the difference in the solvent not significantly affect the survival and growth of common carp seed.